Analisis Model Altman Untuk Memprediksi Kebangkrutan Pada Perusahaan Makanan Dan Minuman - Novia, Susanto Salim (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about effects of Altman Z-Score variable, namely Working Capital to Total Asset, Retained Earnings to Total Asset, Earnings Before Interest and Tax to Total Asset, Market Value Equity to Total Liabilities, andSales to Total AssettoFinancial Distress of the sub-sector food and beverage companies listed in the Indonesia Stock Exchange in the period of 2015-2016. The research is conducted by taking 42 samples using purposive sampling method. The result of this research that Working Capital to Total Asset has a positive significant effect on Financial Distress, Retained Earnings to Total Asset and Earnings Before Interest and Tax to Total Asset has a negative significant effect to Financial Distress, whileMarket Value Equity to Total Liabilities andSales to Total Assethas no significant effect toFinancial Distress